A mysterious cause of chronic cough. Issue 3 (September 2020) - Fereos, George; Buchanan, Charles; Allen, Pamela; Inusa, Baba; Bossley, Cara J.
A 15-year-old-girl of African descent with sickle cell anaemia (HbSS) presented with an 18-month history of gradually worsening productive cough. She had a history of a previous pneumonia, acute chest crises and two episodes of acute pancreatitis. She was on regular blood transfusions. She underwent a splenectomy in December 2013. There was no documented history of hypercalcaemia. She had no history of fevers or tuberculosis (TB) contacts. This case alerts professionals to take a broad approach when considering childhood chronic cough in sickle cell disease. Certain respiratory conditions are difficult to recognise in childhood, with many children suffering from delayed diagnosis. https://bit.ly/2GZAgmE